Through the Prism of the Senses : Mediation and New Realities of the Body in Contemporary Performance. Technology, Cognition and Emergent Research-Creation Methodologies /: Mediation and New Realities of the Body in Contemporary Performance. Technology, Cognition and Emergent Research-Creation Methodologies. (2019) - Choinière Isabelle; Pitozzi Enrico; Davidson Andrea
No abstract available